Jambi Cultur Potential in Mathematics Learning: Jambi’s Ethnomathematic - Sutrimo Sutrimo; Kamid Kamid; Asrial Asrial; Bambang Hariyadi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
This study aims to identify the potential of Jambi culture that can be used as a learning resource in learning mathematics. The focus of the study is to identify culture in the form of objects so that it can be observed and used as an example of modeling mathematical arithmetic concepts. Researchers used a qualitative research approach with ethnographic methods. The research findings were analyzed using descriptive analysis. Based on the findings, there are several Jambi cultures that can be used as learning resources with an ethnomathematical approach, that are; Community work, community arts and crafts, traditional ceremonies, dance movements, music rhythms, folk games, temple relics. Implementation of this research, researchers can give advice in using material culture to be used as a source of learning mathematics. The novelty in this study is that the temple heritage is a Jambi culture that has the potential to be used as a source of learning mathematics.